Smart jewelry design, aesthetics and innovation in the digital age - MATCAN-LISENCO, Inga (Journal of Social Sciences)
This research analyzes the integration of smart jewelry, which combines fashion with technology, meeting the functional and aesthetic requirements of the 21st century. These advanced accessories, equipped with features such as health monitoring and Bluetooth/NFC connectivity, require a multidisciplinary approach in the design process. The study emphasizes the balance between aesthetic appeal and utility, highlighting the use of recyclable materials and classifying jewelry into four distinct categories, each with specific advantages and challenges. It also investigates the impact of emerging technologies on jewelry design and current trends, demonstrating how these innovations are transforming the accessories industry. Relevant examples from renowned jewelers and companies are presented to illustrate sophisticated designs and wireless interactions. Additionally, innovations such as the StreetSmart app and the Project BLAID device highlight their contribution to the mobility of individuals with visual impairments. In conclusion, smart jewelry represents a significant expression of contemporary trends in fashion and technology, offering new opportunities for IoT connectivity and design flexibility.